EFFECT OF POUNDED DAWADAWA (PARKIA BIGLOBOSA) POD HUSK EXTRACT ON STRONGYLE IN WEST AFRICAN DWARF (WAD) GOATS - Octhere, G. V; Naandam, J. (UDS International Journal of Development, 2015)
A preliminary study was conducted to assess residual effect of Dawadawa (Parkia biglobosa) Pod Husk Extract (DPHE) on strongyle ova counts in West African Dwarf (WAD) goats. Eight nanny WAD goats (four per treatment) were used. The study lasted for eighteen days between the month of December 2011 and January 2012. DPHE was prepared by pounding and soaking (1kg/1.5litres of water) and mixture was allowed to stand for 12hours. The filtrate (DPHE solution) was administered orally, 0.6ml/kg of body weight (BW) to the 4 goats (treated goats) as against no DPHE in the 4 control goats (non-treated goats). Faecal samples were taken from the treated goats before administration of DPHE and every three days thereafter up to the 18th day for laboratory analysis of strongyle ova. A two-tail t test was used to analyze the data. Eggs per gram of faeces from the treated goats showed no significant difference (p>0.05) from day 3 to 9 but decreased significantly (p<0.05) from day 12 to 18. The dosage of 0.6ml/kg BW of DPHE resulted in 26% reduction in ova count of treated goats compared with a 13% increase in control goats with reference to the base counts for the given period of the study. What about residual effect?